2006
DOI: 10.1016/j.juro.2006.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Can Phyllanthus niruri Affect the Efficacy of Extracorporeal Shock Wave Lithotripsy for Renal Stones? A Randomized, Prospective, Long-Term Study

Abstract: Regular self-administration of P. niruri after extracorporeal shock wave lithotripsy for renal stones results in an increased stone-free rate that appears statistically significant for lower caliceal location. Its efficacy and the absolute lack of side effects make this therapy suitable to improve overall outcomes after extracorporeal shock wave lithotripsy for lower pole stones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 20 publications
0
35
0
4
Order By: Relevance
“…Tsai et al (2008) (Kumaran & Patki, 2011). Comprovou-se diminuição da supersaturação da urina e a expulsão de cálculos (Mohanty et al, 2010;Erickson et al, 2011). Karmakar & Patki, (2010) realizaram metaanálise de 50 estudos clínicos envolvendo 3037 pacientes, nos quais os tratamentos variavam de duas semanas a dois anos.…”
Section: Principais Plantas Medicinais Com Potencial Uso No Controle unclassified
See 2 more Smart Citations
“…Tsai et al (2008) (Kumaran & Patki, 2011). Comprovou-se diminuição da supersaturação da urina e a expulsão de cálculos (Mohanty et al, 2010;Erickson et al, 2011). Karmakar & Patki, (2010) realizaram metaanálise de 50 estudos clínicos envolvendo 3037 pacientes, nos quais os tratamentos variavam de duas semanas a dois anos.…”
Section: Principais Plantas Medicinais Com Potencial Uso No Controle unclassified
“…niruri tem sido avaliada para prevenção e dissolução de cálculos (Barros et al, 2003; Micali et al, 2006;Shanbhag et al, 2010). Por apresentar propriedade uricosúrica, é de grande interesse no controle de hiperuricemia.…”
Section: Planta Medicinalunclassified
See 1 more Smart Citation
“…Micali and coworkers (37) observed that patients submitted to extracorporeal shock wave lithotripsy and treated with Phyllanthus niruri during 3 months presented lower incidence of residual stone fragments, mainly those in lower calyceal location compared with non-treated patients. According to these investigators, the efficacy and the lack of side effects of Phyllanthus help improve overall outcomes after extracorporeal shock wave lithotripsy and could be useful as either an alternative or an adjunctive therapy in the treatment of urolithiasis.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…P. niruri belongs to the family Euphorbiaceae and can be used to treat kidney stones [13] and disorders of the gastrointestinal and genitourinary tracts [14].…”
Section: Introductionmentioning
confidence: 99%